2018
DOI: 10.1016/j.jpeds.2017.10.074
|View full text |Cite
|
Sign up to set email alerts
|

Access to High Pediatric-Readiness Emergency Care in the United States

Abstract: A significant proportion of US children do not have timely access to EDs with high pediatric readiness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 25 publications
1
62
0
Order By: Relevance
“…For most rural and remote communities, the closest ED is part of a Critical Access Hospital (CAH) that treats a low volume of pediatric patients and as a result may be challenged to have all of the resources needed to care for children. In fact, nearly two‐thirds of children cannot readily access an ED that is highly compliant with pediatric emergency care guidelines . There were 1,326 certified CAHs in 45 states in 2015, treating over 7 million people in the ED, of which approximately one‐fifth (1.46 million) were pediatric patients .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For most rural and remote communities, the closest ED is part of a Critical Access Hospital (CAH) that treats a low volume of pediatric patients and as a result may be challenged to have all of the resources needed to care for children. In fact, nearly two‐thirds of children cannot readily access an ED that is highly compliant with pediatric emergency care guidelines . There were 1,326 certified CAHs in 45 states in 2015, treating over 7 million people in the ED, of which approximately one‐fifth (1.46 million) were pediatric patients .…”
mentioning
confidence: 99%
“…In fact, nearly two-thirds of children cannot readily access an ED that is highly compliant with pediatric emergency care guidelines. 7 There were 1,326 certified CAHs in 45 states in 2015, treating over 7 million people in the ED, of which approximately one-fifth (1.46 million) were pediatric patients. [8][9][10][11] Improving the infrastructure of CAHs to have equipment, medications, policies, and trained personnel to provide safe, quality pediatric emergency care including responding to children in disasters or in mental health crises, or to be able to transfer children when needed, is essential to promoting the health and well-being of children and their families in rural communities.…”
mentioning
confidence: 99%
“…These lower‐pediatric‐volume EDs have been noted to be less “pediatric ready” when measured by a national survey . A recent report noted that 30% of U.S. children do not live within a 30‐minute drive time to an ED with high pediatric readiness …”
mentioning
confidence: 99%
“…Additionally, the Emergency Medical Services for Children (EMSC) has been active in enhancing GED readiness to care for children through changes in policy and procedure. Despite advances in national pediatric readiness, two‐thirds of children cannot readily access an ED that is highly compliant with pediatric emergency care, defined as an ED that has a perfect Pediatric Readiness Score (100) . As such, studies have shown uneven care by demonstrating 1) variation in the care of common pediatric illnesses, such as asthma, croup, dehydration, diabetic ketoacidosis (DKA); 2) more aggressive lab testing and increased hospitalization rates; and 3) lower quality of resuscitations in the GED compared to the PED.…”
mentioning
confidence: 99%